2012
DOI: 10.1590/s0102-36162012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Profilaxia do tromboembolismo venoso em cirurgia ortopédica

Abstract: The relevance of prophylaxis of venous thromboembolism and its complications in orthopedic surgery is increasingly significant. This review discusses the pathophysiology of thrombus formation in general and orthopedic surgery, its incidence, pre- disposing factors and complications. It also presents an updated presentation and critique of prophylaxis currently available in our environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…(venous thromboembolism, pressure ulcers, and pneumonia within 30 days). 3 The risk of death remains even after hospital discharge; however, mortality rates varied greatly in the literature consulted. A study conducted in Brazilian hospital in 2007 observed mortality of up to 36% 24 months after fracture, and 60% 48 months after the occurrence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(venous thromboembolism, pressure ulcers, and pneumonia within 30 days). 3 The risk of death remains even after hospital discharge; however, mortality rates varied greatly in the literature consulted. A study conducted in Brazilian hospital in 2007 observed mortality of up to 36% 24 months after fracture, and 60% 48 months after the occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Compararam-se pacientes que apresentaram óbito intra-hospitalar (grupo caso) com pacientes que não apresentaram óbito hospitalar (grupo controle) quanto à exposição a fatores de risco prévios à lesão e fatores relacionados ao tratamento ortopédico. Resultados: Os fatores relacionados a uma maior taxa de mortalidade intra-hospitalar foram: gênero masculino (grupo caso: 52%; controle: 26%; p = 0,005), menor escore de Parker (grupo caso: 5,0 pontos; controle: 6,2 pontos; p = 0,048), delirium na admissão (grupo caso: 26%; controle: 10%; p = 0,011); delirium desenvolvido durante a internação (grupo caso: 77%; controle: 35%; p < 0,001), e tempo até a cirurgia (13,3 dias vs. 9,1 dias; p = 0,049). Conclusão: No presente estudo, a taxa de mortalidade intra-hospitalar em pacientes com fratura proximal do fêmur foi de 8%, e os principais fatores de risco associados a esse desfecho foram o gênero masculino, escore de…”
Section: Introductionunclassified
“…VTE is the most frequent postoperative complication in general orthopedic surgery, resulting in significant morbidity and mortality [1]. While VTE can develop after any major surgery, the incidence of VTE among orthopedic patients is substantially higher, particularly among recipients of hip and knee arthroplasty [2,3]. Underlining the importance of prevention and prophylaxis, the mortality of pulmonary embolism (PE) following diagnosis may be as high as 30%, particularly among the geriatric population [4].…”
Section: General Principlesmentioning
confidence: 99%
“…A utilização de bota de retorno venoso e as meias compressivas no paciente cirúrgico, no intraoperatório e pós-operatório, mostram-se eficazes no que diz respeito à prevenção de TVP, visto que auxiliam o fluxo sanguíneo e, consequentemente, diminuem a estase venosa, um dos fatores de risco para o desenvolvimento da trombose [16][17] . Alguns participantes da pesquisa citaram o uso de meias compressivas quando possível, caso não tenha contraindicação para determinado paciente.…”
Section: |unclassified